Synuclein Regulates Synaptic Vesicle Clustering and Docking at a Vertebrate Synapse - Fouke, Kaitlyn E.; Wegman, M. Elizabeth; Weber, Sarah A.; Brady, Emily B.; Román-Vendrell, Cristina; Morgan, Jennifer R. (Frontiers in Cell and Developmental Biology, 2021)
Neurotransmission relies critically on the exocytotic release of neurotransmitters from small synaptic vesicles (SVs) at the active zone. Therefore, it is essential for neurons to maintain an adequate pool of SVs clustered at synapses in order to sustain efficient neurotransmission. It is well established that the phosphoprotein synapsin 1 regulates SV clustering at synapses. Here, we demonstrate that synuclein, another SV-associated protein and synapsin binding partner, also modulates SV clustering at a vertebrate synapse. When acutely introduced to unstimulated lamprey reticulospinal synapses, a pan-synuclein antibody raised against the N-terminal domain of -synuclein induced a significant loss of SVs at the synapse. Both docked SVs and the distal reserve pool of SVs were depleted, resulting in a loss of total membrane at synapses. In contrast, antibodies against two other abundant SV-associated proteins, synaptic vesicle glycoprotein 2 (SV2) and vesicle-associated membrane protein (VAMP/synaptobrevin), had no effect on the size or distribution of SV clusters. Synuclein perturbation caused a dose-dependent reduction in the number of SVs at synapses. Interestingly, the large SV clusters appeared to disperse into smaller SV clusters, as well as individual SVs. Thus, synuclein regulates clustering of SVs at resting synapses, as well as docking of SVs at the active zone. These findings reveal new roles for -synuclein at the synapse and provide critical insights into diseases associated with -synuclein dysfunction, such as Parkinson’s disease.